Optical module to extend any Fourier-domain optical coherence tomography system into a polarisation-sensitive system. (6th May 2016) - Rivet, Sylvain; Marques, Manuel J; Bradu, Adrian; Podoleanu, Adrian
Abstract: This article presents a theoretical study on an optical module (OM) that can be inserted between an object under investigation and a Fourier-domain optical coherence tomography system, transforming the latter into a polarisation-sensitive optical coherence tomography optical coherence tomography (OCT) system. The module consists of two electro-optic modulators, a Faraday rotator, a linear polariser and a quarter-wave plate. A detailed description on how the module can be used to extract both the net retardance and the fast axis orientation of a linear birefringent sample is presented. This is achieved by taking two sequential measurements for different values of retardance produced by the electro-optic modulator. The module keeps measurements free from undesired polarimetric effects due to birefringence in the single-mode optical fibre and diattenuation in fibre-based couplers within OCT systems. Simulations have been carried out in order to evaluate the effects of chromatic behaviour of the components within the OM.